Development of a Landing Mechanism for Asteroids with Soft Surface - Zhijun Zhao; Jingdong Zhao; Hong Liu (International Journal of Aerospace Engineering)
A landing mechanism to an asteroid with soft surface is developed. It consists of three landing feet, landing legs, cardan element, damping element, equipment base, anchoring system, and so on. Static structural analysis and modal analysis are carried out to check the strength and natural frequency of the landing mechanism with FEA. Testing platform for the anchoring system is introduced, and then the penetrating and anchoring tests of the anchoring system are carried out in different media. It shows that cohesion of the media has large influence on the penetrating and anchoring performance of the anchoring system. Landing tests of the landing mechanism with different velocities under simulated microgravity environment are carried out on the air-floating platform, and the impact accelerations are measured by the sensors on the landing mechanism. At the same time, these impact accelerations are processed by spectrum analysis to find the natural frequency of the landing mechanism.